2020
DOI: 10.3390/diagnostics10030129
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Disease is More Severe in Patients with Non-Alcoholic Steatohepatitis than Fatty Liver

Abstract: Non-alcoholic fatty liver disease (NAFLD) is associated with a higher risk of atherosclerotic disease. However, the relationships between the severity of coronary atherosclerosis and pathologic findings in patients with NAFLD remain unknown. We aimed to characterize the coronary artery lesions in patients with NAFLD using coronary computed tomography angiography (CCTA). Overall, 101 patients with liver biopsy-proven NAFLD who had chest pain or electrocardiographic abnormalities underwent CCTA. Coronary artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 35 publications
1
21
0
3
Order By: Relevance
“…The association between hepatic fibrosis and the risk of CVD in patients with NAFLD has been reported in several studies 9,11,25‐28 . NASH‐related fibrosis is associated with increased small dense low‐density lipoprotein and oxidised phospholipids leading to oxidative stress and mitochondrial damage, which may also increase the risk of atherosclerosis 29,30 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The association between hepatic fibrosis and the risk of CVD in patients with NAFLD has been reported in several studies 9,11,25‐28 . NASH‐related fibrosis is associated with increased small dense low‐density lipoprotein and oxidised phospholipids leading to oxidative stress and mitochondrial damage, which may also increase the risk of atherosclerosis 29,30 .…”
Section: Discussionmentioning
confidence: 91%
“…Most clinical studies have demonstrated this association using non‐invasive assessment for fibrosis based on indirect serum biomarkers, such as NFS and FIB‐4 index 25,26 . Only a few studies have demonstrated an association of hepatic fibrosis with the risk of CVD in patients with biopsy‐proven NAFLD 9,11,27 . To the best of our knowledge, this is the first study to evaluate the association of CAC with MRE‐determined liver stiffness in patients with NAFLD.…”
Section: Discussionmentioning
confidence: 94%
“…Our study finding could partially explain that few studies analyzing the relationship between NAFLD and CAD, and they present controversial results, which may be due to different spectrums of NAFLD severity [ 26 ]. As for the mechanism underlying the positive relationship between severe NAFLD and CAD, abnormal insulin resistance, inflammation with oxidative stress and endothelial dysfunction may play an important pathway for the development of atherosclerosis with a potential dose–response relationship [ 5 , 6 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this analysis of 10 studies, the initial definition of CVD varied by author. Zheng, et al defined CV disease as carotid intima media thickening > 0.8 mm along with post-exercise brachial-ankle pulse wave velocity as surrogates for clinical cardiovascular disease [20]. Yun, et al, Harring, et al and Hwang, et al defined cardiovascular mortality via ICD 10 codes.…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD is a multifactorial disease that develops from the interactions of genetics, diet, and lifestyle [5,6,20,21]. NAFLD and CVD both have significant similarities in terms of risk factors, genetic predispositions, and pathophysiology.…”
Section: Incidence and Prevalence Of Cardiovascular Events And Mortalitymentioning
confidence: 99%